Associations of Blood Pressure with Body Composition among Afro-Caribbean Children in Barbados - Gaskin, Pamela S.; Hall, Ryan V.; Chami, Peter; St. John, Margaret A.; Gaskin, David A.; Molaodi, Oarabile R.; Harding, Seeromanie (PloS one, 2015)
Despite complex presentation of adult hypertension and a concomitant obesity epidemic, little is known about overweight in relation to blood pressure among Caribbean children. We examined blood pressure in relation to body size in a cross-sectional study of 573 Barbadian children aged 9-10 years (2010-2011). The United States normative blood pressure percentiles were used to identify children with high (≥95th percentile) or high normal blood pressure (90th-95th percentile). The World Health Organization body mass index cut-off points were used to assess weight status. Thirty percent of children were overweight/obese. Percentage fat mass differed between girls (20.4%) and boys (17.72%) (p<0.05). Mean systolic blood pressure among girls was 106.11 (95% CI 105.05, 107.17) mmHg and 105.23 (104.09, 106.38) for boys. The percentages with high or high-normal mean systolic blood pressure were 14.38% (10.47, 18.29) for girls and 8.08% (4.74, 11.41) for boys. Height and body mass index were independent correlates of systolic and diastolic blood pressure. Mean systolic blood pressure was related to lean mass but not fat mass, while diastolic blood pressure was associated with fat mass index and overweight. One third of 9-10 year old children in Barbados were overweight/obese and 12% had elevated mean systolic blood pressure. BP was related to body size. These findings signal potential adverse trends in weight gain and BP trends for children growing up in the context of a country that has recently undergone rapid economic transition.